2017
DOI: 10.35609/jmmr.2017.2.3(16)
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Consumer Decision-making Processes Regarding the Adoption of Mobile Payments: A Qualitative Study

Abstract: Objective - The main objective of this study is to gain deeper understanding on the decision-making process of how and why consumers are adopting mobile payment in Indonesia. Methodology/Technique - The study was a qualitative study that included an experiment to the research design. A total of six young people were voluntarily participated in the study. Our finding provides explanation of salient factors that might drive or hinder the adoption in five different stages of innovation-diffusion process. Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[4] argues that the Technology Acceptance Model can effectively explain users' adoption behaviour towards new technologies, so a TAM-based study was conducted in combination with NFC payments, and the results of the data analysis showed that the better the match between NFC payments and users' pre-existing values, the stronger the willingness to accept them. [1] selected a sample for the study in order to explore the reasons for the small proportion of mobile payment software use in Indonesia, and the results showed that trust was the most important reason affecting individual use.…”
Section: Research On 'Mobile Payments'mentioning
confidence: 99%
“…[4] argues that the Technology Acceptance Model can effectively explain users' adoption behaviour towards new technologies, so a TAM-based study was conducted in combination with NFC payments, and the results of the data analysis showed that the better the match between NFC payments and users' pre-existing values, the stronger the willingness to accept them. [1] selected a sample for the study in order to explore the reasons for the small proportion of mobile payment software use in Indonesia, and the results showed that trust was the most important reason affecting individual use.…”
Section: Research On 'Mobile Payments'mentioning
confidence: 99%